2018
DOI: 10.1080/02770903.2018.1424192
|View full text |Cite
|
Sign up to set email alerts
|

Tiotropium added to low- to medium-dose inhaled corticosteroids (ICS) versus low- to medium-dose ICS alone for adults with mild to moderate uncontrolled persistent asthma: A systematic review and meta-analysis

Abstract: Tiotropium as a once daily add-on to low- to medium-dose ICS may be efficacious and well-tolerated treatment in adults with moderate uncontrolled asthma. However, as only a few studies were identified, more studies of better design and long-term trial duration are required in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…46 Furthermore, in another systematic review of 3 RCTs of approximately 900 school-age children, tiotropium significantly improved lung function and decreased the number of patients with at least 1 exacerbation compared with placebo. 45 Finally, consistent with our findings, a pooled analysis of safety data from trials in adolescents and children with symptomatic moderate asthma found that the most commonly reported AEs with tiotropium treatment included asthma worsening, exacerbations, decreased PEF, nasopharyngitis, viral respiratory tract infection, and respiratory tract infection. 48,49 Limitations of our findings include inadequate data regarding the efficacy and safety of tiotropium in preschool children.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…46 Furthermore, in another systematic review of 3 RCTs of approximately 900 school-age children, tiotropium significantly improved lung function and decreased the number of patients with at least 1 exacerbation compared with placebo. 45 Finally, consistent with our findings, a pooled analysis of safety data from trials in adolescents and children with symptomatic moderate asthma found that the most commonly reported AEs with tiotropium treatment included asthma worsening, exacerbations, decreased PEF, nasopharyngitis, viral respiratory tract infection, and respiratory tract infection. 48,49 Limitations of our findings include inadequate data regarding the efficacy and safety of tiotropium in preschool children.…”
Section: Discussionsupporting
confidence: 89%
“…24 Findings from the present systematic review, like those from systematic reviews of the adult tiotropium trials, reinforce the efficacy and safety of tiotropium in adolescents and children (Supplementary Video 1). 33,44,45 Furthermore, by being able to evaluate all 7 phase 2/3 RCTs of tiotropium as add-on LAMA therapy conducted in children and adolescents with asthma that is uncontrolled despite ICS use, our findings confirm and expand on previously published systematic reviews. 46,47 In a systematic review and meta-analysis of the 3 RCTs of approximately 1000 adolescents (mean age, 14 years) with moderate to severe asthma, tiotropium was deemed well tolerated and efficacious as add-on therapy to maintenance ICS treatment or an ICS plus a LABA.…”
Section: Discussionsupporting
confidence: 78%
“…A recent systematic review and meta-analysis reported that tiotropium, an anticholinergic, with low-to medium-dose ICS once daily could be an acceptable option in the treatment of adults with moderate uncontrolled asthma, with improvements in lung function noted. However, it is important to note that no statistically significant differences were found in the two studies analyzed that used the Asthma Control Questionnaire, with relevant heterogeneity detected [39]. Our study also considered long-acting muscarinic antagonists (LAMA) and SAMA in the anticholinergic drug class, while the systematic review considered tiotropium only.…”
Section: Discussionmentioning
confidence: 86%
“…Certainly, the possibility of adding a LAMA instead of the classic controllers to low or moderate doses of ICSs in patients with moderate symptomatic asthma is supported by increasing evidence (Chung, 2015), mainly in patients suffering from fixed airflow obstruction (Lee et al, 2015). Tiotropium bromide as a once-aday add-on to a low-to medium-dose ICS may also be efficacious and well tolerated in adults with moderate uncontrolled asthma (Wang et al, 2019). However, the results of a recent systematic review and meta-analysis confirmed the usefulness of combining a LAMA with an ICS as maintenance therapy in patients aged $12 years with persistent uncontrolled asthma (Sobieraj et al, 2018a).…”
Section: F When Must An Inhaled Corticosteroid Be Added?mentioning
confidence: 99%